MEDIA E-KOMIK TENTANG PERILAKU HIDUP BERSIH DAN SEHAT TERHADAP KEMAMPUAN CUCI TANGAN YANG BENAR PADA SISWA ANAK USIA DINI - Lessy, Kristina (Jurnal Administrasi Pendidikan Indonesia, 2024)
Children in Indonesia, especially those in educational settings, are still vulnerable to various infectious diseases, including diarrhea and respiratory tract infections caused by bacteria and viruses. This study aims to examine the effect of using e-comic media on improving good and correct handwashing skills in early childhood as part of clean and healthy living behavior (PHBS) education. The study used a quantitative approach with a one-group pretest-posttest pre-experimental design. The research subjects were 20 children in group B, aged 5–6 years. The intervention was carried out through learning with e-comic media, with a PHBS theme designed to teach handwashing procedures in accordance with health standards. Data were collected through children's worksheets (LKA), observation sheets, and teacher questionnaires. The t-test results showed a significant difference between the pretest and posttest scores (t = -12.114; p < 0.05), with the average score increasing from 11.50 to 28.00. Although the correlation between the two scores was weak and insignificant (r = 0.206; p = 0.383), the overall improvement in scores indicated the intervention's effectiveness. Observational data showed an increase in children's enthusiasm and handwashing skills, while teachers' responses to the media reached 98%, indicating very effective implementation. These results indicate that e-comic media not only improve cognitive understanding but also support behavioral changes in children. Therefore, e-comic media is recommended as an engaging and educational learning tool in PHBS education at an early age.